Design of a flash analog-to-digital converter using threshold inverter quantization (TIQ) technique - Murni Hasan. (2010)
The analog-to-digital converter (ADC) is an essential part of system-on-chip (SoC) products because it bridges the gap between the analog physical world and the digital logical world. In the digital domain, low power and low voltage requirements are becoming more important issues as the channel length of MOSFET shrinks below 0.25 sub-micron values.